ANALYSIS OF THE RELATIONSHIP BETWEEN ECONOMIC GROWTH AND DEFORESTATION BASED ON THE ENVIRONMENTAL KUZNETS CURVE HYPOTHESIS FOR THE LEGAL AMAZON AT THE BEGINNING OF THE THIRD MILLENNIUM (REMUNOM, 2025)
In recent years, warnings about environmental degradation have gained prominence in news reports and on global political agendas. In the case of Brazil, attention is mainly focused on the Legal Amazon, considered the largest tropical rainforest in the world. Therefore, deforestation in this region presents a serious threat to biodiversity and the provision of environmental services, essential for maintaining global climate conditions. In this sense, the present study aims to understand, through the Environmental Kuznets Curve (ECK) theory, the impacts of economic growth on deforestation in the Legal Amazon from 2002 to 2020. After a literature review of works addressing the relationship between income growth and environmental degradation in the Legal Amazon, and the collection of data with information on GDP per capita – a proxy for economic growth (obtained from the SIDRA-IBGE website) – and three proxies for environmental degradation – Deforestation Rate (km2), Accumulated Deforestation, and Annual Deforestation Increment (obtained from the PRODES-INPE website), a polynomial regression model with panel data was applied to estimate three Environmental Kuznets Curves for the states that comprise the Legal Amazon. After estimation and application of tests for model selection, the results obtained were a normal “U” shape in the cubic function – with fixed effects, both for the relationship between GDP per capita and deforestation rate (km2), and for the relationship between GDP per capita and annual increase in deforestation, and an inverted “N” shape in the quadratic function – with fixed effects, for the relationship between GDP per capita and accumulated deforestation. The results obtained show different CKA shapes than those proposed by the theory, demonstrating, based on the literature review, that there is no standard CKA shape for the Legal Amazon, also indicating limitations to the CKA theory in explaining the relationship between economic growth and environmental degradation.